Graphene thermal interface material and preparation method thereof

The graphene thermal interface material connected through porous graphene units solves the problems of cracking and thermal conductivity of traditional thermal interface materials, achieves high thermal conductivity and compressibility, and is suitable for long-term use of high temperatures.

CN119307237APending Publication Date: 2025-01-14GUANGDONG MORION NANOTECHNOLOGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411492476.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

Due to the presence of dense structure and adhesives, traditional thermal interface materials are prone to cracking and layering, and their thermal conductivity is hindered, so they cannot be used at high temperatures and for a long time.

Method used

The graphene thermal interface material is prepared by connecting porous graphene units. Through reduction and expansion, rewetting, stacking, drying and heat treatment of the graphene oxide original film, a high thermal conductivity and compressible material is formed, avoiding the use of binder.

Benefits of technology

The longitudinal thermal conductivity coefficient ≥100W/mK, thermal resistance ≤0.1K·cm2/W and carbon content ≥99% were achieved. The material has good compression and thermal conductivity, which is suitable for long-term use at high temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119307237A_ABST
    Figure CN119307237A_ABST
Patent Text Reader

Abstract

The invention provides a graphene thermal interface material and a preparation method thereof, the graphene thermal interface material is formed by connecting two or more porous graphene units, the vertical heat conduction coefficient is greater than or equal to 100W / (m.K), the material thermal resistance is less than or equal to 0.1 K.cm < 2 > / W, and the carbon content is greater than or equal to 99%. According to the material, the advantage of high in-plane heat conduction performance of graphene is fully utilized, meanwhile, abundant graphene hole cavities are formed in the microstructure in the vertical direction, good deformation can be achieved when the material is compressed by external force, and the effects of gap filling and heat conduction are achieved; in addition, no binder is used in the whole preparation process of the material, so that thermal conductivity degradation of the product caused by the binder is avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of thermal management, and in particular to a graphene thermal interface material and a preparation method thereof. Background Art

[0002] Thermal interface materials (TIM) are filled between the heat source and the heat sink to solve the thermal management problem in electronic products. Their performance characteristics show high vertical thermal conductivity and low interface thermal resistance, which enables heat to be quickly transferred between the heat source and the heat sink, thereby reducing the impact of temperature on the normal operation of key components such as chips. Most traditional gasket-type thermal interface materials are composed of high molecular polymers (mainly silicone oil) and thermal conductive fillers. The limited filler content (usually 50%-70wt%) prevents them from achieving higher thermal conductivity (>10W / mK); at the same time, the volatilization problem of silicone oil leads to poor aging resistance of the material components, which makes it impossible to use them in electronic products for a long time or at high temperatures.

[0003] Graphene has excellent thermal conductivity (1000-5300W / mK). The in-plane thermal conductivity of commercial graphene thermal conductive film products has reached more than 1500W / mK, which is higher than traditional heat dissipation materials such as silver, copper, and graphite. Taking advantage of this advantage, some technologies coat the surface of the graphene thermal conductive film with an adhesive, arrange the multi-layer graphene thermal conductive film vertically, and then cut it into thermal interface materials of the required thickness. The product has excellent longitudinal thermal conductivity (>50W / mK). However, due to the structural density of the graphene thermal conductive film, it has almost no compression performance, which causes the thermal interface material to crack and delaminate between the graphene films under compression during use, destroying the use of the product; at the same time, due to the presence of the adhesive, the propagation of phonons will be hindered inside the thermal interface material, reducing the thermal conductivity, and uneven adhesive coating can easily cause the thermal interface material to crack and delaminate. Summary of the invention

[0004] Based on the above reasons, the present application provides a graphene thermal interface material and a preparation method thereof to solve one or more technical problems mentioned in the background technology.

[0005] In a first aspect, a graphene thermal interface material is provided: The graphene thermal interface material is formed by connecting two or more porous graphene units. The vertical thermal conductivity of the graphene thermal interface material is ≥100W / (m·K), and the thermal resistance of the material is ≤0.1K·cm 2 / W, carbon content ≥99%.

[0006] In some embodiments, the density of the graphene thermal interface material is 0.1-0.5 g / cm 3 , compressibility ≥80%.

[0007] In a second aspect, a method for preparing a graphene thermal interface material is provided, comprising the following preparation steps: (1) Preparation of graphene oxide original film; (2) reducing and expanding the graphene oxide film to obtain a porous graphene unit; (3) rewetting, stacking, and drying the porous graphene units; (4) The product obtained in step (3) is subjected to heat treatment to obtain a graphene thermal interface material.

[0008] As an embodiment of the second aspect of the present application, after the graphene thermal interface material is obtained by heat treatment, the method further includes cutting the graphene thermal interface material perpendicular to the stacking direction.

[0009] As an embodiment of the second aspect of the present application, the reduction expansion in step (2) includes reduction by a chemical reagent, and the chemical reagent is at least one of hydrazine hydrate, sodium hydrogen borate, dimethylhydrazine, and thiourea.

[0010] As an embodiment of the second aspect of the present application, the mass concentration of the chemical reagent is 0.5~30%.

[0011] As an embodiment of the second aspect of the present application, the rewetting in step (3) includes placing the porous graphene unit in a water vapor environment with a relative humidity of 70-95% for 1-10 minutes.

[0012] As an embodiment of the second aspect of the present application, the drying in step (3) includes vacuum negative pressure drying.

[0013] As an embodiment of the second aspect of the present application, the vacuum pressure of vacuum negative pressure drying is -0.01~-0.1MPa.

[0014] As an embodiment of the second aspect of the present application, the heat treatment in step (4) includes a pretreatment at 170-360°C, a carbonization treatment at 1000-1300°C, and a graphitization treatment at 2500-3200°C, and load pressurization is performed during the pretreatment and / or carbonization treatment and / or graphitization treatment.

[0015] Compared with the prior art, the present invention has at least the following beneficial effects: The carbon chains in the porous graphene unit structure are connected and stacked into a thick film with high thermal conductivity in the plane. The thick film can be flipped 90° or cut to a specified thickness perpendicular to the stacking direction to obtain the required graphene thermal interface material. This material fully utilizes the advantages of high thermal conductivity of graphene in the plane. At the same time, its microstructure has abundant graphene pores arranged in the vertical direction, which enables it to achieve good deformation when compressed by external force, thereby achieving the effect of filling gaps and conducting heat. In addition, no adhesive is used in the entire preparation process of the material, which avoids the attenuation of thermal conductivity of the product caused by the adhesive. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying any creative work.

[0017] Figure 1 is a SEM image of the porous graphene unit prepared in Example 1; Figure 2 This is a physical picture of the product obtained after heat treatment in Example 4; Figure 3 This is a physical picture of the product obtained after heat treatment in Example 5. DETAILED DESCRIPTION

[0018] The following detailed description of exemplary embodiments of the present invention refers to the accompanying drawings, which form a part of the description, in which exemplary embodiments of the present invention are shown as examples, wherein the features of the present invention are identified by reference numerals. The following more detailed description of the embodiments of the present invention is not intended to limit the scope of the claimed invention, but is merely for illustration and does not limit the description of the features and characteristics of the present invention, in order to propose the best way to perform the present invention, and is sufficient to enable those skilled in the art to implement the present invention. However, it should be understood that various modifications and variations may be made without departing from the scope of the present invention as defined by the appended claims. The detailed description and the accompanying drawings should be considered only as illustrative, not restrictive, and if there are any such modifications and variations, they will all fall within the scope of the present invention described herein. In addition, the background technology is intended to illustrate the current status and significance of the research and development of the present technology, and is not intended to limit the present invention or the application field of the present application and the present invention.

[0019] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which the present invention belongs; the terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention; the term "and / or" used herein includes any and all combinations of one or more related listed items.

[0020] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.

[0021] In order to make the technical problems, technical solutions and advantages to be solved by the present invention more clear, a detailed description will be given below with reference to the accompanying drawings and specific embodiments.

[0022] Graphene has been developed as a variety of thermal management materials due to its excellent in-plane thermal conductivity. In the prior art, an adhesive is coated between traditional graphene films, and multiple layers of traditional graphene thermal conductive films are arranged vertically and then cut into thermal interface materials of required thickness. However, due to the density of the traditional graphene film structure, the thermal interface material is prone to cracking and delamination, and due to the poor compression and rebound ability of the traditional graphene film, it cannot play a buffering and filling role. At the same time, the adhesive will block the propagation of phonons inside the thermal interface material, reducing the thermal conductivity of the thermal interface material. Uneven adhesive coating can also easily lead to cracking and delamination of the thermal interface material.

[0023] The first aspect of the present application provides a graphene thermal interface material: The graphene thermal interface material is formed by connecting two or more porous graphene units. The vertical thermal conductivity of the graphene thermal interface material is ≥100W / (m·K), and the thermal resistance of the material is ≤0.1K·cm 2 / W, carbon content ≥99%. The main material of the graphene thermal interface material is carbon. The mass fraction of carbon and its orderly arrangement play a decisive role in the thermal conductivity of the graphene thermal interface material. Its carbon content ≥99%, on the one hand, guarantees the thermal conductivity of the material, and at the same time, it shows that the material has less impurities, does not contain adhesives, has low thermal resistance, and has better thermal conductivity.

[0024] In some embodiments of the present application, the density of the graphene thermal interface material is 0.1-0.5 g / cm 3 , compressibility ≥ 80%. The density of traditional graphene film is 1.8~2.2g / cm 3The density of graphene thermal interface material is strong, and it basically has no compression rebound performance. When used as a thermal interface material, it is easy to produce delamination and cracking, and because it has no compression rebound performance, it cannot play a role in filling gaps. The applicant found that the density of graphene thermal interface material is controlled at 0.1~0.5g / cm 3 , which can ensure that its compressibility is ≥80% and has compression rebound effect. If the density is less than 0.1g / cm 3 The thermal interface material is brittle and easily collapses when subjected to stress. If the density is greater than 0.5 g / cm 3 , the compression rebound performance becomes worse.

[0025] A second aspect of the present application provides a method for preparing a graphene thermal interface material, comprising the following preparation steps: (1) Preparation of graphene oxide original film; (2) reducing and expanding the graphene oxide film to obtain a porous graphene unit; (3) rewetting, stacking, and drying the porous graphene units; (4) The product obtained in step (3) is subjected to heat treatment to obtain a graphene thermal interface material.

[0026] In some embodiments of the present application, after the graphene thermal interface material is obtained by heat treatment, the step of cutting the graphene thermal interface material perpendicular to the stacking direction is also included. The thickness of the graphene thermal interface material obtained in the above step (4) is equal to the length / width of the original graphene oxide film. Nowadays, electronic devices are developing in the direction of being lighter and thinner. The reserved gap in the electronics that can accommodate the thermal interface material is generally small. Therefore, the graphene thermal interface material in step (4) can be cut perpendicular to the stacking direction to obtain a thermal interface material with customized thickness.

[0027] In some embodiments of the present application, the reduction and expansion of graphene oxide is carried out by reducing with chemical reagents, and the chemical reagents are at least one of hydrazine hydrate, sodium hydrogen borate, dimethylhydrazine, and thiourea. On the one hand, the above chemical reagents can transform the dense layers of original graphene oxide membrane into a microstructure containing a large number of holes; on the other hand, the reduction of chemical reagents is weaker than high-temperature reduction methods such as graphitization. The edges of the reduced graphene oxide membrane also have carbon-oxygen (hydroxyl, carboxyl) and carbon-hydrogen (hydrogen) ends, which provide a basis for the subsequent connection between the porous graphene unit layers.

[0028] In some embodiments of the present application, the mass concentration of the chemical reagent is 0.5-30%. If the concentration is too low, an effective micro-nano pore structure cannot be formed, and if the concentration is too high, most of the oxygen-containing groups will be reduced, affecting the connection between subsequent porous graphene unit layers.

[0029] In some embodiments of the present application, the rewetting in step (3) includes placing the porous graphene unit in a water vapor environment with a relative humidity of 70-95% for 1-10 minutes. The porous graphene unit needs to be dried again and then rewetted for stacking. If the porous graphene units in a wet state are directly stacked, the porous graphene and the chemical reagents are still in a reaction state to release a large amount of heat. The stacking of multiple porous graphene sheets causes heat accumulation, which can easily burn the product; and the porous graphene units do not have active sites in a dry state and cannot be connected between layers. The purpose of rewetting the porous graphene units is to rely on the action of water to reactivate the chemical activity of the block surface, mainly to produce or restore active groups such as hydroxyl (-OH) and carboxyl (-COOH) in the GO structure, which make the block units form a tight connection due to the esterification reaction between the two after stacking.

[0030] In some embodiments of the present application, the drying in step (3) includes vacuum negative pressure drying. The purpose of this step is not only to achieve conventional baking and drying, but also to help the water molecules produced by the esterification reaction between the block units to completely and quickly leave the reaction surface and become irrecoverable. Compared with the conventional baking and drying method to remove ordinary water, vacuum negative pressure drying can remove most forms of water molecules in the material (including free water, bound water, crystalline water, etc.), which can further enhance the connection between the graphene micro-nanocavity block units.

[0031] In some embodiments of the present application, the vacuum pressure of vacuum negative pressure drying is -0.01~-0.1MPa.

[0032] In some embodiments of the present application, the heat treatment in step (4) includes a pretreatment at 170-360°C, a carbonization treatment at 1000-1300°C, and a graphitization treatment at 2500-3200°C. During the pretreatment and / or carbonization and / or graphitization, weight pressure is applied. Graphitization promotes the rearrangement and connection between graphene carbon atoms. With the assistance of weight, the carbon atoms on the surface of the graphene intermediates are more easily "welded" together. At the same time, during the heat treatment, the film material undergoes a dramatic volume expansion due to the release of a large amount of gas due to the removal of functional groups. In the absence of pressure, the film material will expand several times in the height direction, and the expansion coefficient is uncontrollable, resulting in uncontrollable thickness of the final finished graphene thermal conductive film.

[0033] In the embodiment of the present application, the test method for the graphene thermal interface material is as follows: Performance testing of graphene thermal interface materials: Among them, the test method of longitudinal thermal conductivity is: cut the sample into a disc with a diameter of about 12.7mm, measure and record its thickness, place it in a 4 samples round / 12.7mm bracket, and put it into the NETZSCH 467 instrument for testing. The test environment temperature is set to 25-27℃, the temperature threshold (tolerance / stability threshold) is 0.3K, the number of flash points is 5, the voltage is 260V, the pulse width is 44μs, the main gain is adjusted to 6633, the sampling time is adjusted to 6ms, the detection area is 3.7mm, and the parameter optimization is turned on. After the test, the average longitudinal thermal conductivity data of each group of samples is recorded, and the thermal conductivity = thermal diffusion coefficient * density * 0.85.

[0034] The test method for thermal resistance is: refer to the test standard ASTM D5470 "Standard Test Method for Thermal Transfer Properties of Thermally Conductive Electrical Insulating Materials", and test it through a thermal conductivity tester, model number is Ruiling LW-9389.

[0035] The carbon content test method is: tested by X-ray electron spectrometer, model ESCAlab250, test conditions: basic pressure is 3×10 -8 In the Pa energy analysis mode, A1 Kα 1486.8 eV X-rays were used as the excitation source to test the chemical composition of the samples.

[0036] The density testing method is: refer to the formula, density = mass / volume.

[0037] The compression performance test method is: through the universal material testing machine test, the sample is cut into a size of 35mm*35mm, placed between the compression test heads with a diameter of 80mm, the material thickness corresponding to the target compression amount is set, and pressure is applied to it at a pressing speed of 12.5mm / min. The final appearance damage of the test material is observed to determine the compressibility. Example 1

[0038] A 5% solid content GO slurry was coated on a PET substrate with a coating thickness of 2000 μm. After drying at 40°C, 45°C, 60°C, and 80°C, the original graphene oxide (GO) film was obtained by peeling. The graphene unit is placed in a 1wt% hydrazine hydrate solution and dried to obtain a graphene unit with rich multi-level pores. The structure of the porous graphene unit is as follows: Figure 1 As shown; After the porous graphene unit was rehumidified with 85% humidity water vapor for 3 minutes, 60 porous graphene units were stacked with a total stack thickness of 50 mm, and placed in an oven with a vacuum degree of -0.1 MPa at 100°C until completely dried to obtain an intermediate; Then, the intermediate was pretreated at 170°C for 6 hours, carbonized at 1200°C for 3 hours, and graphitized at 3000°C for 2 hours, and during the graphitization process, a weight 100 times the weight of the intermediate was loaded on the surface of the intermediate; Finally, laser cutting is used to slice along the stacking direction, and the slice thickness is 0.2 mm to obtain the graphene thermal interface material of the required thickness.

[0039] The test results show that the carbon content of the product is 99.75%, the longitudinal thermal conductivity is 110 W / mK, and the thermal resistance is 0.06Wcm 2 / K, density is 0.21g / cm 3 , the compressibility is 92%. Example 2

[0040] This group of embodiments differs from Embodiment 1 in that 10 wt % of dimethylhydrazine is used in step (2) to foam and reduce the original graphene oxide film, and the other steps are consistent with Embodiment 1.

[0041] The test results show that the carbon content of the product is 99.82%, the longitudinal thermal conductivity is 115 W / mK, and the thermal resistance is 0.056Wcm 2 / K, density is 0.17g / cm 3 , the compressibility is 95%. Example 3

[0042] This group of embodiments differs from Embodiment 1 in that 28 wt % of hydrazine hydrate is used in step (2) to foam and reduce the original graphene oxide film, and the other steps are consistent with Embodiment 1.

[0043] The test results show that the carbon content of the product is 99.79%, the longitudinal thermal conductivity is 115 W / mK, and the thermal resistance is 0.088Wcm 2 / K, density is 0.13g / cm 3 , the compressibility is 98%. Example 4

[0044] This group of examples is different from Example 1 in that, in step (3), after the surface of the graphene block unit is rewetted with 70% humidity water vapor for 10 minutes, 5 porous graphene units are stacked, with a total stack thickness of 4 mm, and placed in an oven with a vacuum degree of -0.05 MPa at 100°C until completely dried to obtain an intermediate. The other steps of this example are consistent with Example 1. The product after heat treatment is as follows Figure 2 shown.

[0045] The test results show that the carbon content of the product is 99.75%, the longitudinal thermal conductivity is 115 W / mK, and the thermal resistance is 0.046Wcm 2 / K, density is 0.26g / cm 3 , the compressibility is 86%. Example 5

[0046] This group of examples is different from Example 1 in that, in step (3), after the surface of the graphene block unit is re-moistened with 95% humidity water vapor for 1.5 minutes, 15 porous graphene units are stacked, with a total stack thickness of 13 mm, and placed in an oven with a vacuum degree of -0.01 MPa at 100°C until completely dried to obtain an intermediate. The other steps of this example are consistent with Example 1. The product after heat treatment is as follows Figure 3 shown.

[0047] The test results show that the carbon content of the product is 99.63%, the longitudinal thermal conductivity is 115 W / mK, and the thermal resistance is 0.041Wcm 2 / K, density is 0.18g / cm 3 , the compressibility is 91%. Example 6

[0048] This group of embodiments is different from Embodiment 1 in that, in step (3), after the porous graphene unit is rehumidified for 3 minutes with 85% humidity water vapor, 60 porous graphene units are stacked, with a total stacking thickness of 50 mm, and then the intermediate is obtained by directly placing the units in an oven at 100° C. to completely dry without setting a vacuum degree. The test results show that the carbon content of the product is 99.35, the longitudinal thermal conductivity is 115 W / mK, and the thermal resistance is 0.07Wcm 2 / K, density is 0.26g / cm 3 , the compressibility is 88%. Example 7

[0049] This group of embodiments is different from Embodiment 1 in that the graphene thermal interface material after pretreatment, carbonization and graphitization is not sliced, that is, the graphene thermal interface material is directly obtained. Example 8

[0050] This group of embodiments differs from Embodiment 1 in that, in step (5), pretreatment at 360°C for 3 h, carbonization at 1000°C for 3 h, and graphitization at 2800°C for 3 h are sequentially performed, and during the graphitization process, a weight 75 times the weight of the body is applied to the surface of the intermediate. The other steps of this embodiment are consistent with those of Embodiment 1.

[0051] The test results show that the carbon content of the product is 99.59%, the longitudinal thermal conductivity is 115 W / mK, and the thermal resistance is 0.021Wcm 2 / K, density is 0.33g / cm 3 , the compressibility is 89%. Comparative Example 1

[0052] (1) GO slurry with a solid content of 5% was coated on a PET substrate with a coating thickness of 2000 μm. After drying at 40°C, 45°C, 60°C, and 80°C, the GO original film was peeled off; (2) The GO original membrane was pretreated at 170°C for 6 h and carbonized at 1200°C for 3 h to obtain a porous graphene unit; (3) After the porous graphene unit was rehumidified with 85% humidity water vapor for 3 minutes, 60 porous graphene units were stacked with a total stacking thickness of 50 mm, and placed in an oven with a vacuum degree of -0.1 MPa at 100°C until completely dried to obtain an intermediate; (4) Further, the intermediate is graphitized at 3000°C for 2 h, and during the graphitization process, a weight 100 times the weight of the intermediate is loaded on the surface of the intermediate; This comparative example failed to prepare a graphene thermal interface material composed of porous graphene units stacked and connected layer by layer. The reason is that the use of carbonization, a high-temperature thermal reduction method, to create pores in the GO original membrane will cause most of its oxygen-containing functional groups to be removed, thereby causing the porous graphene units to lose the basis for esterification reactions between layers, and the target product cannot be obtained. Comparative Example 2

[0053] GO slurry with 5% solid content was coated on a PET substrate with a coating thickness of 2000 μm. After drying at 40°C, 45°C, 60°C, and 80°C, the original GO film was peeled off. The graphene unit is placed in a 1wt% hydrazine hydrate solution to obtain a graphene unit with rich multi-level pores; When the porous graphene unit is still in a wet state of hydrazine hydrate infiltration, 60 porous graphene units are stacked with a total stack thickness of 50 mm. The stack is placed in an oven with a vacuum degree of -0.1 MPa at 100°C for drying. The sample is directly burned during the drying process.

[0054] This comparative example failed to prepare a graphene thermal interface material composed of porous graphene units stacked layer by layer. The reason is that the porous graphene units in a wet state are directly stacked, and the porous graphene and chemical reagents are still in a reaction state to release a large amount of heat. The stacking of multiple sheets of porous graphene causes heat accumulation and burns the product. Comparative Example 3

[0055] (1) A 5% solid content GO slurry was coated on a PET substrate with a coating thickness of 2000 μm. After drying at 40°C, 45°C, 60°C, and 80°C, the original graphene oxide (GO) film was obtained by peeling it off; (2) placing it in a 1wt% hydrazine hydrate solution for treatment and drying to obtain a graphene unit with rich multi-level pores; (3) Stack 60 porous graphene units with a total stacking thickness of 50 mm, and place them in an oven with a vacuum degree of -0.1 MPa at 100 °C until they are completely dried to obtain an intermediate; (4) Then, the intermediate body was subjected to a pretreatment at 170°C for 6 h, carbonization at 1200°C for 3 h, and graphitization at 3000°C for 2 h, and during the graphitization process, a weight 100 times the weight of the intermediate body was applied to the surface of the intermediate body.

[0056] This comparative example failed to prepare a graphene thermal interface material composed of porous graphene units stacked and connected layer by layer. The reason is that the dried porous graphene units were not rewetted. Water can reactivate the surface chemical activity of the porous graphene units, but without the effect of water, there is no basis for esterification reaction between the porous graphene units, and the target product cannot be obtained. Comparative Example 4

[0057] (1) A 5% solid content GO slurry was coated on a PET substrate with a coating thickness of 2000 μm. After drying at 40°C, 45°C, 60°C, and 80°C, the original graphene oxide (GO) film was obtained by peeling it off; (2) Further, the GO original film was pretreated at 170°C for 6 hours, carbonized at 1200°C for 3 hours, and graphitized at 3000°C for 2 hours. During the graphitization process, a weight 100 times the weight of the body was loaded on the surface of the intermediate, and a graphene thermal conductive film was obtained after calendering. (3) coating the surface of the obtained graphene thermal conductive film with an adhesive, and then stacking 60 sheets of the graphene thermal conductive film layer by layer to obtain a thick block of graphene thermal interface material; (4) Finally, laser cutting is used to slice the graphene thermal interface material along the stacking direction. The slice thickness is 0.2 mm to obtain the graphene thermal interface material of the required thickness.

[0058] The test results show that the carbon content of the product is 80.36%, the longitudinal thermal conductivity is 89.3 W / mK, and the thermal resistance is 0.26Wcm 2 / K, density is 1.52g / cm3, and compressibility is 58%.

[0059] In the above embodiments, the description of each embodiment has its own emphasis. For parts that are not described in detail in a certain embodiment, reference can be made to the relevant descriptions of other embodiments.

[0060] The above is a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can easily think of various equivalent modifications or replacements within the technical scope disclosed by the present invention, and these modifications or replacements should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope of the claims.

Claims

1. A graphene thermal interface material, characterized in that: The graphene thermal interface material is formed by connecting two or more porous graphene units. The vertical thermal conductivity of the graphene thermal interface material is ≥100W / (m·K), and the thermal resistance of the material is ≤0.1K·cm 2 / W, carbon content ≥99%.

2. The graphene thermal interface material according to claim 1, characterized in that: The density of the graphene thermal interface material is 0.1-0.5 g / cm 3 , compressibility ≥80%.

3. A method for preparing a graphene thermal interface material, characterized in that: The preparation method comprises the following steps: preparing a graphene oxide original film; The graphene oxide film is reduced and expanded to obtain a porous graphene unit; rewetting, stacking, and drying the porous graphene units; The product obtained in step (3) is heat-treated to obtain a graphene thermal interface material.

4. The method for preparing the graphene thermal interface material according to claim 3, characterized in that: After the obtained graphene thermal interface material is heat-treated, the method further includes cutting the graphene thermal interface material perpendicular to the stacking direction.

5. The method for preparing the graphene thermal interface material according to claim 3, characterized in that: The reduction expansion in step (2) includes reduction by a chemical reagent, wherein the chemical reagent is at least one of hydrazine hydrate, sodium hydrogen borate, dimethylhydrazine, and thiourea.

6. The method for preparing the graphene thermal interface material according to claim 5, characterized in that: The mass concentration of the chemical reagent is 0.5-30%.

7. The method for preparing the graphene thermal interface material according to claim 3, characterized in that: The rewetting in step (3) comprises placing the porous graphene unit in a water vapor environment with a relative humidity of 70 to 95% for 1 to 10 minutes.

8. The method for preparing the graphene thermal interface material according to claim 3, characterized in that: The drying in step (3) includes vacuum negative pressure drying.

9. The method for preparing the graphene thermal interface material according to claim 8, characterized in that: The vacuum pressure of the vacuum negative pressure drying is -0.01~-0.1MPa.

10. The method for preparing the graphene thermal interface material according to claim 3, characterized in that: The heat treatment in step (4) includes a pretreatment at 170-360° C., a carbonization treatment at 1000-1300° C., and a graphitization treatment at 2500-3200° C., and load pressurization is performed during the pretreatment and / or carbonization and / or graphitization treatment.

Citation Information

Cited By

  • Thermal conduction structure and electronic assembly

    TWI931320B